Factors Influencing the Level of Knowledge of Reproductive Age Women about Visual Inspection with Acetic Acid (VIA Test) at PMB S. April - May Period in 2023 - Sartika, Dewi Sartika; Sarimalini, Masayu Delta; Widiyanti, Wiwi (Rajaki of Tulip Medika Publisher, 2023)
Background: Cervical cancer is a disease caused by sexually acquired infection with Human Papiloma Virus (HPV) sub-types, especially sub-types 16 and 18 (WHO, 2016). IVA is an examination of the cervix (cervix) by looking directly (naked) at the cervix after wiping the cervix with a 3-5% acetic acid solution. Based on data from the Indonesian cancer foundation, in Indonesia 1 hour 1 person dies from cervical cancer and 34.4 per cent of cancers in women. The number of new cases of cervical cancer is 40 to 45 per day. Purpose: To find out what factors influence the level of knowledge of WUS on knowledge about VIA test in PMB S period April-May 2023? Methods: The design used was a survey with a